Use of Transposon Directed Insertion-Site Sequencing to Probe the Antibacterial Mechanism of a Model Honey on E. coli K-12 - Masoura, Maria; Milner, Mathew T.; Overton, Tim W.; Gkatzionis, Konstantinos; Lund, Peter A. (Frontiers in Microbiology, 2022)
Antimicrobial resistance is an ever-growing health concern worldwide that has created renewed interest in the use of traditional anti-microbial treatments, including honey. However, understanding the underlying mechanism of the anti-microbial action of honey has been hampered due to the complexity of its composition. High throughput genetic tools could assist in understanding this mechanism. In this study, the anti-bacterial mechanism of a model honey, made of sugars, hydrogen peroxide, and gluconic acid, was investigated using genome-wide transposon mutagenesis combined with high-throughput sequencing (TraDIS), with the strain Escherichia coli K-12 MG1655 as the target organism. We identified a number of genes which when mutated caused a severe loss of fitness when cells were exposed to the model honey. These genes encode membrane proteins including those involved in uptake of essential molecules, and components of the electron transport chain. They are enriched for pathways involved in intracellular homeostasis and redox activity. Genes involved in assembly and activity of formate dehydrogenase O (FDH-O) were of particular note. The phenotypes of mutants in a subset of the genes identified were confirmed by phenotypic screening of deletion strains. We also found some genes which when mutated led to enhanced resistance to treatment with the model honey. This study identifies potential synergies between the main honey stressors and provides insights into the global antibacterial mechanism of this natural product.